Hubungan Panjang Tungkai Dengan Hasil Lompat Jauh Pada Materi Atletik Kids Kelas V Sd Negeri 1 Kalioso Kabupaten Kudus - Abdullah Efendi (Tunas Nusantara, 2022)
The formulation of the problem in this study is how is the relationship between leg length and long jump results in the athletic material of the fifth grade kids at SD Negeri 1 Kalioso Kudus Regency? The research method used in this research is descriptive correlational method. The research sample was taken using a total sampling technique, namely the total number of students in grade V SD Negeri 1 Kalioso Kudus Regency, totaling 12 people. The instruments used were the leg length measurement method and the long jump test on the athletic material of the kids. From the research results obtained tcount = 0.363 at a significant level α = 0.05 and n = 12, then dk = 12-2 = 23 so that t table = 0.352, the result is tcount ≥ t table or 0.363 ≥ 0.352, then H0 is rejected, meaning that there is a relationship significant between the leg length variable and the long jump result. Thus it can be argued that the hypothesis that the author formulated, namely "There is a significant relationship between leg length and long jump results in the athletic material of the fifth grade kids at SD Negeri 1 Kalioso Kudus Regency, for the academic year 2021/2022.